Understanding Financial Management Among Generation Z: The Roles of Islamic Financial Literacy, Fintech Usage, and Lifestyle - Waasi, Nur; Samsul; Mustamin, Asyraf; Ridho, M Taufik (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2026)
This study aims to analyze the Influence of Islamic Financial Literacy and the Use of Financial Technology on Generation Z Financial Management with Lifestyle as a Moderation Variable. The research was conducted by quantitative method through an associative approach. Data collection was carried out by distributing questionnaires to 200 FEBI students of the 2021-2024 batch. The data obtained is processed using SPSS. The results of the study show that Islamic financial literacy and the use of fintech have a significant positive effect on the financial management of Generation Z. Lifestyle also has a significant effect on the financial management of Generation Z, but it is not able to moderate the influence of Islamic financial literacy and the use of fintech on the financial management of Generation Z. Practically, the results of this study affirm the urgency of increasing Islamic financial literacy and the wise use of fintech. and indicates that the influence of lifestyle on the relationship between the two is independent.